Spaces and Character's Behaviour in Trees of Peace Film: A Literary Spatial Analysis - Akhmad Zakky; Balya Mikaela Rahmah (Universitas Islam Negeri Sunan Gunung Djati, 2026)
This research aims to analyse the relationship between the space and the women characters behaviour, and how the characters interpret the spaces in Trees of Peace film. The spatial triad by Henri Lefebvre was employed to answer the research questions while using qualitative method to analyse the data that are collected from the film’s scenes and dialogues. The research found that a character’s behaviour in a small space can vary, and can be very distinct from one character and another. How the characters interpret the spaces can also varies, depending on the situations and experiences that each character had gone through, even when they are spending time in the same place. The dynamic of the character also caused the difference in interpreting the space. As a result, the relationship between the characters and the space are intertwined with how they interpret the space. The better relationship a character has with the space, the more positive their interpretation of the space will be. Keywords: Space, Spatial Triad, Trees of Peace Film, Women.